2000
DOI: 10.1001/jama.284.23.3015
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Moderate Weight Change and Sleep-Disordered Breathing

Abstract: Our data indicate that clinical and public health programs that result in even modest weight control are likely to be effective in managing SDB and reducing new occurrence of SDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
825
4
96

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,570 publications
(981 citation statements)
references
References 61 publications
56
825
4
96
Order By: Relevance
“…This is a clinically relevant issue, as it could in turn complicate the management of this disease for which weight loss happens to be an efficient therapy. 101 SMR measured -SMR predicted …”
Section: Organochlorines: Obesogen Pollutants?mentioning
confidence: 97%
“…This is a clinically relevant issue, as it could in turn complicate the management of this disease for which weight loss happens to be an efficient therapy. 101 SMR measured -SMR predicted …”
Section: Organochlorines: Obesogen Pollutants?mentioning
confidence: 97%
“…Among these, obesity is one of the strongest sleep apnea risk factors (12)(13)(14)(15). Mild to moderate obesity has been associated with markedly increased sleep apnea prevalence (3,14,16). In a community-based cohort of middle-aged subjects, Young and colleagues (1) showed that a 1-SD increase in BMI was associated with a fourfold increased risk for prevalent sleep apnea, and we have demonstrated a sleep apnea prevalence of approximately 40% in moderately overweight men from the community who are otherwise healthy (3).…”
Section: Sleep Apnea Risk Factors: Roles Of Obesity Sex Fat Distribmentioning
confidence: 99%
“…40 kg/m 2 ), the prevalence of sleep apnea was estimated to vary between 40 and 90% (17)(18)(19)(20)(21)(22)(23)(24), and the severity of sleep apnea was generally greater than that found in leaner clinical populations (17,25,26). In addition, Peppard and colleagues have provided further evidence for a link between sleep apnea and obesity by demonstrating that a 10% change in body weight was associated with a parallel change of approximately 30% in the apnea-hypopnea index (AHI), the major index of sleep apnea severity (16).…”
Section: Sleep Apnea Risk Factors: Roles Of Obesity Sex Fat Distribmentioning
confidence: 99%
“…3,4 In the USA, more than 80% of the estimated deaths attributable to obesity occurred among individuals with body mass index (BMI) of X30, 5 and in 2004 the prevalence of BMI of X30 was 32% among adults aged 20 years or older. 6 In Japan, the prevalence of BMI X30 in 2004 was much lower at 3% among adults aged 15 years or older.…”
Section: Introductionmentioning
confidence: 99%